Adsorption efficiency of banana blossom peels (musa acuminata colla) adsorbent for chromium (VI) removal. (2022) - Selimin, M.A.; Latif, A.F.A.; Er, Y.C.; Muhamad, M.S.; Basri, H.; Lee, T.C.
Abstract: The discharge of waste from industries into water has caused heavy metal pollution posing health risk to biota such as lead and chromium (VI). Once the water has been polluted, it will limit the accessibility to clean freshwater. Therefore, this paper aims to evaluate the adsorption efficiency of banana blossom peels for the chromium (Cr) (VI) removal under different pH (1, 4, 7, and 10). Extraction of banana blossom peels adsorbent was carried out via chemical treatment using 0.1 M of HCI and 5% (w/v) NaOH solution. The morphology and functional groups of extracted banana blossom peels adsorbent were then characterized using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), and subsequently, the Cr (VI) removal efficiency was examined using ultraviolet–visible spectroscopy (UV–VIS). The extracted banana blossom peels adsorbent is found to have wavy surface with shallow dents. Results demonstrated that adsorbent at pH 10 have the optimum removal of Cr (VI) with 18.87% followed by pH 7 (18.36%), pH 4 (12.28%) and pH 1 (12.00%) after 8 h. The maximum Cr (VI) adsorption capacity is 227.27 mg/g. In this study, the pseudo-second-order model best describes the adsorption process. Langmuir isotherm model is more favorable with high correlation coefficient of 0.99. In conclusion, adsorbent extracted from banana blossom has the potential to be used for Cr (VI) removal in water sources and reduce disposal of agricultural wastes by transforming it into a valuable material.